Similar effects on sediment structure and infaunal community of two competitive intertidal soft-bottom burrowing crab species - Martinetto, Paulina Maria del Rosario (2011)
The intertidal crabs Neohelice granulata and Cyrtograpsus angulatus are common on the south-west Atlantic coast but they rarely share the same microhabitat. They are similar in size and in several life history traits which promote competition. Neohelice granulata is the dominant species in intertidal soft-sediment and salt-marsh areas from southern Brazil to northern Patagonia Argentina, where it forms extensive burrowing beds. Its burrowing activity affects sediment characteristics as well as the infaunal community. When both species coexist N. granulata constrains the distribution and modifies some population characteristics and burrowing behaviour of C. angulatus. However, C. angulatus live in burrows forming dense burrowing beds in soft-bottom intertidal areas where N. granulata is absent. Where both species coexist, C. angulatus rarely constructs burrows and N. granulata clearly dominate soft-sediment areas forming conspicuous burrowing beds. This suggests that these crab species could have similar ecological roles in some effects on sediments related to burrowing activities. In this study, we experimentally compare their effects on sediment characteristics and infaunal community. The results of the experiment showed that C. angulatus modify sediment water and organic matter contents and grain size-frequency distributions similarly to N. granulata. Neither N. granulata nor C. angulatus affected the mean abundance of infaunal organisms during the experiment but their variances showed the same patterns in many cases, indicating similar effects. These results indicate that C. angulatus can modify sediment characteristics similarly to N. granulata, and has similar interactions with infaunal species.